Successful Pessary Use During Pregnancy: Report of Three Cases - Sezen Bozkurt Köseoğlu; Aytekin Tokmak; Metin Kaba (Gynecology Obstetrics & Reproductive Medicine)
The success in use of pessary during pregnancy for preterm birth risk and prolapse of uteri is promising. There are limited data about the use of pessary during pregnancy in the literature. In current report, we assessed to present three pregnant women managed by same type of pessary successfully. All cases were in the second trimester of their pregnancies. One of the cases had subtotal uterine prolapse and the others were under risk of preterm birth.